A girl's guide to moving on : a novel - Macomber, Debbie (New York : Ballantine Books, 2016)
An ex- daughter-in-law and mother-in-law become unlikely best friends. Nichole is recovering after learning that her husband was having an affair. Leanne, Nichole's mother -in-law, gathers the courage to leave her husband, and the two women support one another in rebuilding their lives and embracing surprising new romantic endeavours.
Keywords: Man-woman relationships -- Fiction; Female friendship -- Fiction; Marital conflict -- Fiction; Adultery -- Fiction; Sagas -- Fiction; Love stories